Management and Organizational Culture of Pesantren in Java:: Analysis of Ethnography and Institutional Image - Teguh Luhuringbudi; Fitri Liza; Achmad Yani; Dewi Nita Utami (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The objective of this research is to uncover the management model and organizational culture of pesantren (Islamic boarding schools) in Java. The study is based on ethnographic categories, namely urban and rural Islamic boarding schools, institutional system image categories, namely modern and traditional Islamic boarding schools. The research methodology involves library research for data sources and collection, and qualitative research for data analysis. The aim of using Lucia Mudiningtias' (2022) Islamic Boarding School Integration Management theory is to analyse internal capability indicators, such as finance, human resources, and organisational professionalism. Additionally, Muhammad Thoyib's (2018) theory of Contemporary Multicultural Islamic Education is used to analyse external capabilities, including community relations and the degree of nationalism. This research draws two conclusions, including: 1) Urban, rural, modern and traditional Islamic boarding schools in Java have the potential to improve and develop finances, risk management, cooperatives, work ethic, and increase the competence of educational staff; and 2) The text discusses urban, rural, modern, and traditional Islamic boarding schools in Java, focusing on their interaction with local communities, decision-making inefficiencies, cases of istiqāmah-qanā'ah in work, and the lack of career paths for teaching staff. Additionally, external elements such as the community can be involved, and teaching staff can be delegated to various educational and social services in the surrounding community. Annual periodic training, managerial counseling, and human resource empowerment for ustadz and ustadzah can also be implemented.